Gastric Syphilis: Differential diagnosis with Gastric Carcinoma – A case report - Bento, Ana Sofia; Baptista, Hamilton Neves; Silva, Mário Rui; Oliveira, Fernando José Serra; Martinho, Fernando Jaime (Revista Portuguesa de Cirurgia; No 10 (2009): Setembro 2009 - II Série, 2009)
.